THE INFLUENCE OF WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE ENGAGEMENT AT DINAS KOPERASI PERINDUSTRIAN DAN PERDAGANGAN KOTA MALANG - Lukitaningtias, Firina; Atiwi, Erna; Kirom, Novita Rifaul; Awa, Starce Septiani Ole (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study aims to understand how the work environment and compensation affect employee engagement at Dinas Koperasi Perindustrian dan Perdagangan Kota Malang. Data from 80 respondents were collected using questionnaires and analyzed using multiple linear regression analysis with SPSS 23 software. The results show that the work environment has a positive and significant influence on employee engagement, while compensation does not have a significant influence. However, collectively, the work environment and compensation have a significant impact on employee engagement. These findings highlight the importance of creating a supportive work environment and improving compensation strategies to enhance employee engagement in the organization.